Association Between CT Angiogram Collaterals and CT Perfusion in the Interventional Management of Stroke III Trial. Issue 2 (February 2016) - Vagal, Achala; Menon, Bijoy K.; Foster, Lydia D.; Livorine, Anthony; Yeatts, Sharon D.; Qazi, Emmad; d'Esterre, Chris; Shi, Junzi; Demchuk, Andrew M.; Hill, Michael D.; Liebeskind, David S.; Tomsick, Thomas; et al.
Abstract : Background and Purpose—: Collateral flow can determine ischemic core and tissue at risk. Using the Interventional Management of Stroke (IMS) III trial data, we explored the relationship between computed tomography angiogram (CTA) collateral status and CT perfusion (CTP) parameters. Methods—: Baseline CTA collaterals were trichotomized as good, intermediate, and poor, and CTP studies were analyzed to quantify ischemic core, tissue at risk, and mismatch ratios. Kruskal–Wallis and Spearman tests were used to measure the strength of association and correlation between CTA collaterals and CTP parameters. Results—: A total of 95 patients had diagnostic CTP studies in the IMS III trial. Of these, 53 patients had M1/M2 middle cerebral artery±intracranial internal carotid artery occlusion, where baseline CTA collateral grading was performed. CTA collaterals were associated with smaller CTP measured ischemic core volume ( P =0.0078) and higher mismatch ( P =0.0004). There was moderate negative correlation between collaterals and core ( r s =−0.45; 95% confidence interval, −0.64 to −0.20) and moderate positive correlation between collaterals and mismatch ( r s =0.53; 95% confidence interval, 0.29–0.71). Conclusion—: Better collaterals were associated with smaller ischemic core and higher mismatch in the IMS III trial. Collateral assessment and perfusion imaging identify the same biological construct about ischemic tissue sustenance.